2005
DOI: 10.2169/internalmedicine.44.188
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Worsened Encephalopathy after Intravenous Glycerol Therapy in Patients with Adult-onset Type II Citrullinemia (CTLN2)

Abstract: Objective We report a risk of worsening of encephalopathy by glycerol infusion when this osmotic agent is used for the treatment of brain edema in patients with adult-onset type II citrullinemia (CTLN2) caused by citrin deficiency.Patients and Methods We performed a retrospective investigation of 3 patients with CTLN2 treated for brain edema at our institute: a 31-year-old male patient and a 40-year-old female patient received treatment for encephalopathy-related brain edema with 10% glycerol infusion and 20% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 23 publications
1
45
0
Order By: Relevance
“…This is in contrast to CTLN1 patients or those with other urea cycle disorders, where dietary intake of protein is typically restricted to prevent the build up of ammonia from protein degradation (59). Furthermore, there have been several clinical reports of glucose, glycerol, or fructose infusion as a therapy for hyperammonemia and brain edema in CTLN2 patients that resulted in an enhanced hyperammonemia and a rapid deterioration (31)(32)(33). Based on these clinical observations, we challenged the Ctrn/mGPD double knock-out mice with an oral FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to CTLN1 patients or those with other urea cycle disorders, where dietary intake of protein is typically restricted to prevent the build up of ammonia from protein degradation (59). Furthermore, there have been several clinical reports of glucose, glycerol, or fructose infusion as a therapy for hyperammonemia and brain edema in CTLN2 patients that resulted in an enhanced hyperammonemia and a rapid deterioration (31)(32)(33). Based on these clinical observations, we challenged the Ctrn/mGPD double knock-out mice with an oral FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CTLN1 or other urea cycle enzyme deficiencies typically are given restricted protein diets to minimize episodes of hyperammonemia resulting from protein degradation. In contrast, several CTLN2 patients have developed severe hyperammonemia or deterioration following an intravenous infusion of a high glucose solution (31,32) or an administration of glycerol and fructose for the treatment of brain edema (33). Furthermore, we have observed a citrin deficiency patient who exhibited an increased blood ammonia level following a typical hospital meal but showed no increase following a meal rich in protein and fat.…”
mentioning
confidence: 81%
“…Other features shown in NICCD patients are hypoproteinemia, hypoglycemia, hemolytic anemia, a-fetoproteinemia, fatty liver, and/or mild liver dysfunction. The clinical data from CTLN2 or NICCD patients have been described Yazaki et al 2004Yazaki et al , 2005Tazawa et al 2004;Hachisu et al 2005) and will be reported elsewhere. In addition to DNA samples from 1,372 Japanese, 1,008 Chinese, 1,314 Taiwanese, and 201 Korean controls Saheki et al 2004), the dried spot blood specimens collected at newborn screening centers (54 in Liaoning, 302 in Shandong, 175 in Henan, 200 in Hubei, 638 in Guangdong, and 2,254 in Korea) were anonymized and used as controls without selection.…”
Section: Patients and Control Individualsmentioning
confidence: 99%
“…This peculiar fondness is noted from their early childhood (Hachisu et al 2005). Infusions of large amounts of carbohydrate including glycerol may be harmful for patients with citrin deficiency, and a high carbohydrate diet may trigger CTLN2 (Imamura et al 2003;Saheki et al 2004;Yazaki et al 2005). Discrepancy in CTLN2 incidence may be related to variations in food customs.…”
Section: The Origin Of Mutation [I] or [Ii] Alleles In East Asia Postmentioning
confidence: 99%
“…Generally speaking, the prognosis of patients with CTLN2 is not favorable after the onset of encephalopathy, and liver transplantation is required for severe CTLN2 which is refractory to various ammonia-lowering and neuroprotective therapies. Furthermore, certain types of conventional treatments for brain edema, such as intravenous administration of hyperosmotic and high sugar solutions, have been reported to aggravate encephalopathy [2,10,11], and the mechanism of toxicity of carbohydrate overload for citrin deficiency has been recently clarified using mouse models [12]. Thus, early diagnosis of citrin deficiency and CTLN2 and appropriate treatment might improve prognosis.…”
Section: Introductionmentioning
confidence: 99%